Petroleum catalysis in nontechnical language - Magee, John S. (Penn Well, 1998)
Catalysis is literally the heart of many petroleum refining processes and therefore of ongoing interest to those in and around the refining industry. In easy-to-grasp language and format, Petroleum Catalysis in Nontechnical Language examines fluid catalytic cracking (FCC), reforming, hydrotreating, hydrocracking, isomerization, and polymerization, as well as catalysts of the future such as enzymes.